2022
DOI: 10.1007/s40122-022-00400-1
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Parecoxib for Pain Relief after Orthopedic Surgery: A Systematic Review and Meta-analysis

Abstract: Introduction Orthopedic procedures have been associated with increased pain, making perioperative analgesia a major clinical concern. We assessed the efficacy and safety of intravenous parecoxib administration during the perioperative period for postoperative pain relief after orthopedic surgery in adults. Methods PubMed, Cochrane Library, EMBASE, and clinicaltrial.gov were searched from inception to 23 August 2021 without language restrictions. Randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It inhibits the aggregation of leukocytes, reduces the formation of bradykinin, inhibits platelet agglutination, and induces apoptosis and anti-angiogenesis by selectively inhibiting the activity of COX-2, thus producing antipyretic, analgesic, anti-inflammatory, and anti-cancer effects ( Kaduševičius, 2021 ). Studies have shown that in major surgeries such as thoracic surgery and orthopedics, parecoxib sodium can reduce pain levels and postoperative serum inflammatory factor levels, reduce the incidence of adverse reactions such as nausea and vomiting and pulmonary infections, reduce analgesic drug consumption, reduce hemodynamic instability, and reduce surgery-related stress reactions ( Yang et al, 2020 ; Li et al, 2022a ). Basic research has revealed that parecoxib sodium can exert neuroprotective effects by inhibiting and improving mitochondrial dysfunction in the substantia nigra via the COX-2/PGE2 pathway ( Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits the aggregation of leukocytes, reduces the formation of bradykinin, inhibits platelet agglutination, and induces apoptosis and anti-angiogenesis by selectively inhibiting the activity of COX-2, thus producing antipyretic, analgesic, anti-inflammatory, and anti-cancer effects ( Kaduševičius, 2021 ). Studies have shown that in major surgeries such as thoracic surgery and orthopedics, parecoxib sodium can reduce pain levels and postoperative serum inflammatory factor levels, reduce the incidence of adverse reactions such as nausea and vomiting and pulmonary infections, reduce analgesic drug consumption, reduce hemodynamic instability, and reduce surgery-related stress reactions ( Yang et al, 2020 ; Li et al, 2022a ). Basic research has revealed that parecoxib sodium can exert neuroprotective effects by inhibiting and improving mitochondrial dysfunction in the substantia nigra via the COX-2/PGE2 pathway ( Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few meta-analyses have been conducted to investigate the efficacy and safety of parecoxib or flurbiprofen axetil for perioperative analgesia in children, but evidence in adults is constantly being updated. A previous meta-analysis by Li et al ( 68 ) reported that low to moderate evidence indicated that parecoxib relieved postoperative orthopedic pain while sparing opioid analgesic consumption without increasing the incidence of adverse events ( 68 ). Sun et al ( 69 ) reported that the perioperative administration of flurbiprofen was effective in reducing postoperative pain, nausea, and vomiting in Chinese surgical patients ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite this fact, research on IV NOA in the orthopedic field is relatively scarce compared to other areas. In 2022, in the field of orthopedic surgery, Li et al reported a meta-analysis about the effects of IV parecoxib following overall orthopedic surgery [25]. They finally included 27 articles that dealt with general orthopedic surgery, but only three of them addressed hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%